2016
DOI: 10.1038/emi.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Has Rift Valley fever virus evolved with increasing severity in human populations in East Africa?

Abstract: Rift Valley fever (RVF) outbreaks have occurred across eastern Africa from 1912 to 2010 approximately every 4–15 years, most of which have not been accompanied by significant epidemics in human populations. However, human epidemics during RVF outbreaks in eastern Africa have involved 478 deaths in 1998, 1107 reported cases with 350 deaths from 2006 to 2007 and 1174 cases with 241 deaths in 2008. We review the history of RVF outbreaks in eastern Africa to identify the epidemiological factors that could have inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 68 publications
0
49
0
Order By: Relevance
“…, Baba et al . ). While this has led to increased vigilance with regard to RVF during disease surveillance, Wesselsbron virus is not routinely considered during arbovirus surveillance exercises.…”
Section: Discussionmentioning
confidence: 97%
“…, Baba et al . ). While this has led to increased vigilance with regard to RVF during disease surveillance, Wesselsbron virus is not routinely considered during arbovirus surveillance exercises.…”
Section: Discussionmentioning
confidence: 97%
“…They reflect a retinal disease, responsible for vision loss with blind spots [6, 14]. The pathogenesis of the lesions is not well understood, but fluorescein angiography suggests that the lesions are often the result of primary occlusion of the retinal circulation, probably as a result of proliferation of virus particles in the endothelial cells [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Diverse ecological factors influence outbreak frequency, whereas virus evolution has a greater impact on its virulence in hosts. The threat to humans posed by the diversified RVF virus strains increases the potential public health and socioeconomic impacts of future outbreaks [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Nipah virus, identified in 1998, is emerging zoonosis that affects both animals and humans [13,[21][22][23][24]. Rift Valley fever is a viral zoonosis that was first identified among sheep on a farm in the Rift Valley of Kenya [25][26][27][28][29]. The WHO committee listed another three pathogens/infectious diseases and considered them as serious and require an action as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review using Pubmed, Google Scholar and Scopus showed that bibliometric studies on SARS or Ebola or Nipah virus have been carried out, but as a single disease and not as a group of diseases with potential future severe epidemics [25][26][27][28][29]. The collective analysis of literature on top eight pathogens will give a more comprehensive view on these infectious diseases and will help identify which one needs to be given top priority for funding and research.…”
Section: Introductionmentioning
confidence: 99%